Sc(OTf)3-Catalyzed [3+3] Annulation of Cyclopropane 1,1-Diesters with β-(Indol-2-yl)-α,β-unsaturated Ketones: Synthesis of Polysubstituted Tetrahydrocarbazoles - Chen, Wei; Zhang, Huan-Huan; Luo, Yong-Chun (Synlett, 2015)
A Sc(OTf)3-catalyzed cascade reaction consisting of a Friedel–Crafts alkylation followed by a Michael addition between cyclopropane 1,1-diesters and β-(indol-2-yl)-α,β-unsaturated ketones allows for the efficient synthesis of polysubstituted tetrahydrocarbazoles under very mild reaction conditions.
Keywords: Lewis acids; scandium; catalysis; annulation; heterocycles